Pathology confirmation of the efficacy and safety of microwave ablation in papillary thyroid carcinoma - Ding, Min; Wu, Gao-Song; Gu, Jian-Hua; Shen, Dong-Jie; Zhou, Rui; Liu, Ying; Xie, Rong-Li; Wang, Shu-Rong; Wang, Hong-Cheng; Fei, Jian (Frontiers in Endocrinology, 2022)
Background: The incidence of papillary thyroid carcinoma (PTC) has rapidly increased in recent years. Microwave ablation (MWA) was proposed as an alternative treatment for PTC. This study aimed to investigate the efficacy and safety of MWA by exploring the postoperative pathology results of post-ablation lesions in patients with PTC. Methods: This study retrospectively analyzed data from 12 patients who underwent thyroid surgery after MWA treatment for primary PTC between January 2015 and November 2021 in six hospitals. Results: The average age of the 12 patients (8 female) was 45.3 ± 9.7 years. There was one patient with PTC (size > 1 cm) and 11 patients with micro-PTC (size ≤ 1 cm), of which eight patients had unifocal micro-PTC and three patients had multifocal micro-PTC. A total of 17 tumor foci with mean size of 6.2 ± 2.6 mm were treated by MWA. The median interval time between MWA and surgery was 6.6 months (range: 0.4–21.9 months). Intraoperatively, adherence to the anterior cervical muscle group was observed in three cases (3/12). Upon postoperative pathologic examination, all the post-ablation lesions of the eight unifocal micro-PTC and two multifocal micro-PTC showed no residual carcinomas. Outside the ablation zone, PTCs were detected in three cases, including two of the eight patients with unifocal micro-PTC and one of the three patients with multifocal micro-PTC. Cervical lymph node metastases were detected in seven patients (7/12). Conclusion: MWA was feasible for the treatment of primary unifocal low-risk micro-PTC (T1aN0M0) with good efficacy and safety. However, the use of MWA for treating PTC (size > 1 cm) and multifocal micro-PTC remains controversial.